2020
DOI: 10.13189/cea.2020.080520
|View full text |Cite
|
Sign up to set email alerts
|

The Cognition of the Architectural Styles Role on Thermal Performance in Houses of Semi-Arid Climates: Analysis of Building Envelope Materials

Abstract: The envelope of buildings has an important role in controlling the energy consumption in buildings. The climatic changes and depletion of conventional sources make this fact important. This paper endeavors to estimate the thermal performance (steady-state) condition of a range of houses envelope with different architectural styles in Northern Iraq. The study examines the potential of the building envelope materials to control heat loss/gain through calculating U-Value (Heat transfer coefficient value). The cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…This approach is widely used in building construction as an energy-efficient technic to determine the optimum insulation thickness where the total cost (i.e. energy cost and the initial cost of the insulation material) is at the minimum [19,25].…”
Section: Previous Studiesmentioning
confidence: 99%
“…This approach is widely used in building construction as an energy-efficient technic to determine the optimum insulation thickness where the total cost (i.e. energy cost and the initial cost of the insulation material) is at the minimum [19,25].…”
Section: Previous Studiesmentioning
confidence: 99%
“…Many studies have shown that the building style in semi-arid climates can have a significant role in building thermal performance conditions [11]. For example, residents of traditional dwellings have different thermal comfort levels than those living in contemporary dwellings, as they encompass special thermal adaptive behaviors [12].…”
Section: Introductionmentioning
confidence: 99%
“…The study region is in the southern part of the Kurdistan region of Iraq, classified as semi-arid, and according to the Köppen-Geiger climate classification system, it has been identified as subtropical steppe (BSh) [19]. The critical season in this area is summer, as it is longer, the temperature arrives at 50 • C in warm months, and the warmer season is longer than the cold season [11,20].…”
Section: Introductionmentioning
confidence: 99%
“…Carbon dioxide emissions from buildings increase because of the direct use of fossil fuels or through electricity which generates from fossil fuels [1]. Thermal comfort performance takes the biggest part of energy consumption in residential buildings [2,3], and consequently increase CO 2 emission from building sectors. Therefore, improving energy consumption retrofit in the buildings has a significant role in mitigation of carbon dioxide emission, and slow down the short-term climatic change [4].…”
Section: Introductionmentioning
confidence: 99%
“…1,2,3,10,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30 Plastic Processing (having 2 compartments), Double Glassed Window (Uncoated Glass), 6mm4,8,9, 11,12 Aluminum Processing Double Glass uncoated Window, 6mm 5 Plastic Processing (Having 2 Compartments), Single Glassed Window with 4mm thickness 6 Aluminum Processing, Single Glassed window with 6mm thickness 7,13 Wooden Processing, Single Glassed window with 6mm thickness…”
mentioning
confidence: 99%